The place and role of modern advocacy of Ukraine in the human rights mechanism - Сопілко, Ірина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article deals with the issue of the role and place of the institute of advocacy in human rights protection system of Ukraine. At the same time an author raises up the issues of advocacy activity and directions of their reform.